(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Arabic is a language that has a highly strict grammatical structure, both in terms of pronunciation, writing and others. The language consists of systematic rules and one of them is writing rule. This term is an important thing that must be considered. In Arabic, writing errors can be fatal, as damaging meanings or even changing meanings into other meanings. Similarly, the rule of using hamzah at the beginning of a sentence. There are several students of high school or even in Arabic department who still make mistake in doing this, as happen to Arabic students’department in UIN Ar Raniry. The purpose of this research is to analyze the students’ ability of Arabic department in UIN Ar Raniry in writing hamzah at the beginning of Arabic words. This research took 128 Arabic students’department in UIN Ar Raniry in 2020/2021 as population. Then, the researcher chose 15 students in unit five to be a sample. This research used descriptive analyze and quantitave method to analyzed the data. In this research, the researcher collected the data from the question’s answer that given by researcher to the resondent. Therefore, this data was analyzed by the researcher through percentage formula. The result showed that the students’ ability of Arabic department in UIN Ar Raniry in writing hamzah at the beginning of arabic words is low. It related to the average value of the correct answer is only 58,66%.